Behavior of DNA fibers stretched by precise meniscus motion control - Otobe, Kazunori (Oxford University Press, 2001)
A modified DNA combing method, which can precisely locate straightened DNA fibers on a substrate, has been developed. Precise motion control of a DNA solution droplet on hydrophobic surfaces has allowed detailed analyses of DNA straightening behavior. Our method provides a technique for consistently straightening λ phage DNA on a trace of droplet motion, though the straightened DNAs had several variations in their alignments. The dependence of the straightened DNA frequency upon motion rate, fluidity in the droplet and environmental humidity was investigated. Visualization of the solution flow in the moving droplet indicated that flows circulating parallel to the contour of the droplet markedly bias the direction of straightening in relation to the site in the droplet. As a result, the alignment variations caused by the site specificity of the bias direction revealed that environmental humidity significantly alters the straightening behavior.